Applications of Fourier transform infrared spectroscopy, Fourier transform infrared microscopy and near-infrared spectroscopy to cancer research. Issue 2 (2003) - Yano Yano, Kazuyuki Kazuyuki; Sakamoto Sakamoto, Yasushi Yasushi; Hirosawa Hirosawa, Narumi Narumi; Tonooka Tonooka, Shouko Shouko; Katayama Katayama, Hiroo Hiroo; Kumaido Kumaido, Kuniyoshi Kuniyoshi; Satomi Satomi, Akira Akira
Abstract : Glycogen levels in human lung and colorectal cancerous tissues were measured by the Fourier transform (FT-IR) spectroscopic method. Reliability of this method was confirmed by chemical analyses of the same tissues used for the FT-IR spectroscopic measurements, suggesting that this spectroscopic method has a high specificity and sensitivity in discriminating human cancerous tissues from noncancerous tissues. The glycogen levels in the tissues were compared with the clinical, histological and histopathological factors of the cancer, demonstrating that glycogen is a critical factor in understanding the biological nature of neoplastic diseases. Furthermore, direct measurement of a very small amount of tissue by a FT-IR microscope suggested that it could be used as a diagnostic instrument for various tissue samples obtained via a fine needle biopsy procedure. The progressive alterations in rat mammary gland tumors were investigated by a near-infrared (NIR) spectrometer with a fiber optic probe. A lipid band due to the first overtone of n -alkane was used to quantitatively evaluate malignant changes in the tumors. NIR spectroscopy may offer the potential for non‒invasive, in vivo diagnosis of human cancers.